Structural characterization of ferric hemoglobins from three Antarctic fish species of the suborder Notothenioidei - VERGARA, ALESSANDRO; FRANZESE, MARISA; MERLINO, ANTONELLO; MAZZARELLA, LELIO; L. VITAGLIANO; G. DI PRISCO; C. VERDE; H. C. LEE; J. PEISACH (Biophysical Journal, 2007)
Spontaneous autoxidation of tetrameric Hbs leads to the formation of Fe (III) forms, whose physiological role is not fully understood. Here we report structural characterization by EPR of the oxidized states of tetrameric Hbs isolated from the Antarctic fish species Trematomus bernacchii, Trematomus newnesi, and Gymnodraco acuticeps, as well as the x-ray crystal structure of oxidized Trematomus bernacchii Hb, redetermined at high resolution. The oxidation of these Hbs leads to formation of states that were not usually detected in previous analyses of tetrameric Hbs. In addition to the commonly found aquo-met and hydroxy-met species, EPR analyses show that two distinct hemichromes coexist at physiological pH, referred to as hemichromes I and II, respectively. Together with the high-resolution crystal structure (1.5 A ̊ ) of T. bernacchii and a survey of data available for other heme proteins, hemichrome I was assigned by x-ray crystallography and by EPR as a bis-His complex with a distorted geometry, whereas hemichrome II is a less constrained (cytochrome b5-like) bis-His complex. In four of the five Antartic fish Hbs examined, hemichrome I is the major form. EPR shows that for HbCTn, the amount of hemichrome I is substantially reduced. In addition, the concomitant presence of a penta-coordinated high-spin Fe (III) species, to our knowledge never reported before for a wild-type tetrameric Hb, was detected. A molecular modeling investigation demonstrates that the presence of the bulkier Ile in position 67beta in HbCTn in place of Val as in the other four Hbs impairs the formation of hemichrome I, thus favoring the formation of the ferric penta-coordinated species. Altogether the data show that ferric states commonly associated with monomeric and dimeric Hbs are also found in tetrameric Hbs.